2010
DOI: 10.1007/s13197-010-0011-7
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient composition of cultivated stevia leaves and the influence of polyphenols and plant pigments on sensory and antioxidant properties of leaf extracts

Abstract: Stevia rebaudiana is an introduced crop in India. The leaf and its extract although sweet have a bitter after taste that precludes commercial acceptability. The composition of the leaf refl ected a high nutritive value and polyphenol concentration averaging 4.15% by weight of dried leaf. Variably processed extracts enriched with polyphenols, pigments and a mixture of both were evaluated for sensory attributes by a semi trained panel when added to cofee and lime juice. Presence of polyphenols infl uenced the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(57 citation statements)
references
References 32 publications
3
49
0
5
Order By: Relevance
“…In our work ash content was similar to reported by Mishra et al [10]. Tadhani and Subhash [6] reported a slightly higher amount of ash content and substantial amount of crude fiber [2,11,12]. Our study have shown the more protein content as compare to Kaushik et al [11] and Abou-Arab et al [13]; whereas, the fat content value was higher than that reported by Serio [4], and a valuable carbohydrate was found.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our work ash content was similar to reported by Mishra et al [10]. Tadhani and Subhash [6] reported a slightly higher amount of ash content and substantial amount of crude fiber [2,11,12]. Our study have shown the more protein content as compare to Kaushik et al [11] and Abou-Arab et al [13]; whereas, the fat content value was higher than that reported by Serio [4], and a valuable carbohydrate was found.…”
Section: Discussionsupporting
confidence: 89%
“…Stevia leaves are a good source of nutritional values regardless of methods of drying. It has been used as a substitute for sugar in place of pure stevioside in different food preparations and its high ash content indicates that the stevia leaves are good source of inorganic minerals [2,11].…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic components are potential antioxidants, free radical terminators (Shahidi and Wanasundara 1992;Kaushik et al 2010). These compounds are the main agents that can donate hydrogen to free radicals and thus break the chain reaction of lipid oxidation at the first initiation step.…”
Section: Total Phenolics and Flavonoid Contentmentioning
confidence: 99%
“…The beneficial effects of these compounds on human health have been previously studied. Research aimed at obtaining Stevia extracts containing significant levels of sweeteners and these compounds (Gawel-Beben et al 2015, Kawshik et al 2010. The results showed that there is still no consensus on the ideal method of obtaining both compounds (sweeteners and bioactive compounds) in significant concentrations.…”
Section: Introductionmentioning
confidence: 99%